2004
DOI: 10.1097/00008390-200412000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma in Taiwan: a prognostic study of 181 cases

Abstract: This study was performed to determine the characteristics and clinical outcome of patients with cutaneous malignant melanoma in Taiwan. The medical records of patients with primary cutaneous melanoma between 1992 and 2001 at Chang Gung Memorial Hospital (CGMH) were retrieved from the cancer registry. Survival was analysed by the Kaplan-Meier method. Univariate and multivariate analyses of factors associated with survival were performed using the Cox proportional hazard model. One hundred and eighty-one cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
96
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 12 publications
16
96
3
3
Order By: Relevance
“…Our study revealed that SSM was lower and ALM was higher compared to western countries. However, our ALM frequency was similar to another study from Turkey but it was not as high as in reported studies from Asian countries (Chang et al, 2004;Tas et al, 2006;Lee et al, 2012). When the histological subtypes which were categorized as ALM and nonALM, it was not associated with DFS and OS for patients with thick melanoma (Fujisawa et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study revealed that SSM was lower and ALM was higher compared to western countries. However, our ALM frequency was similar to another study from Turkey but it was not as high as in reported studies from Asian countries (Chang et al, 2004;Tas et al, 2006;Lee et al, 2012). When the histological subtypes which were categorized as ALM and nonALM, it was not associated with DFS and OS for patients with thick melanoma (Fujisawa et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies from Asia have reported that ALM is the most common form in MM and its frequency is about 50%. (Chang et al, 2004;Lee et al, 2012). The most common histopathological form in our study was SSM (37.9%), followed by NM (26.2%) and ALM (13.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age in other studies is slightly lower than our 65.3 years (from 55.9 [13] to 61 years [14]). The proportion of ALM of all melanoma in other studies ranges from 41.8% [15] to 85.9% [9], therefore the reported 8/10 "likely ALM" reported here is within the reported range of the region.…”
Section: Discussioncontrasting
confidence: 79%
“…Nevertheless, assuming a best-case scenario for all other patients, we have at best an 8/ 10 patient 6-month survival in this series, compared with an overall 80.3% 5-year survival rate of ALM in a study from the USA. We note, however, 5-year survival rates from studies in Asian countries are typically 41%−49% [9,14,15]. This is likely to be a direct result of the late presentation and late stage of the patients in this series.…”
Section: Acral Melanoma In Cambodiamentioning
confidence: 70%
“…Despite comprising only 2%-10% of all melanomas, acral melanoma is the most frequent subtype in patients of African, Middle Eastern, and Asian descent [9][10][11]. Acral melanoma confers a worse overall prognosis compared with cutaneous melanomas in Western series (largely in the preipilimumab/BRAF inhibitor era), although this negative effect is not clear in Asian studies [9,[12][13][14][15][16].The spectrum and frequency of genetic alterations in this subtype is distinct from cutaneous melanoma; KIT mutations occur more commonly (15%-20% vs. 1%), BRAF V600 mutations arise less often (15% vs. 45%-50%), and NRAS mutations are found at similar incidence (15%-20%) [17,18]. Accordingly, no genotype-specific treatments are available for many patients, thus making ipilimumab and other immune therapies the principal therapeutic strategy for patients with advanced acral melanoma.…”
Section: Introductionmentioning
confidence: 99%